Impact of Extrinsic Job Satisfaction Factors on Organizational Commitment of Banking Sector at Pokhara Metropolis - Budathoki, Dhruba Kumar (Journal of Nepalese Business Studies, 2023)
The paper aims at examining the influence of extrinsic JS factors on organizational commitment of employees in banking sector of Pokhara Metropolis. Non-managerial employees of government, joint- and non-joint venture commercial banks comprising 102 males and 107 females were approached for opinion survey. A questionnaire consisting of five-point Likert scales along with demographic questions were disseminated to collect the data. Using descriptive and analytical method, the results were obtained. The results revealed that a high level of extrinsic job satisfaction appeared when employees have friendly relation with supervisors, while they were least satisfied with pay. It implies that banking employees get satisfied if their supervisor treats them as friends. The study also found those employees’ emotional feelings like loyalty, and having an affiliation with their organization was enthusiastic. Similarly, they believe better to stay in the current organization as the organization has providing something for them, because leaving current organization will need extra costs for them. Thus, there was a higher position of affective commitment and moderate level of continuance and normative commitment of employees. Finally, it was found that extrinsic job satisfaction dimensions have constructive significant impact of employees’ commitment at work place, indicating a high level of extrinsic factors play a pivotal role to satisfy the banking employee and thereby their organizational commitment. The study contributes to analyze extrinsic job satisfaction factors in banking sectors and which factor play significant role to create their commitment of employees in workplace.